Robert Mugabe and the betrayal of Zimbabwe - Norman, Andrew, 1943- (Jefferson, N.C. : McFarland Publishers, 2004)
Instead of leading his people to the "promised land," Mugabe, the first prime minister of the newly-named Zimbabwe, has amassed a fortune for himself, his family and followers and has presided over the murder, torture and starvation of those who oppose him. This biography offers some explanations for Mugabe's behavior. With the death of his wife in 1992, a moderating influence was lost, and as the years go by, he continues to show himself intolerant of any opposition as he proceeds toward the creation of a one-party state, even though evidence suggests that his country is in terminal decline.
Origins of southern Rhodesia -- Mugabe's early life -- Mugabe's formative years -- Imprisonment -- Freedom and exile -- The Lancaster House Conference -- Victory for Mugabe and ZANU-Pf -- The land question -- The movement for democratic change -- Mugabe tightens his grip -- Disaster looms -- The Earth Summit and beyond -- Cricket and coercion -- In perspective : the phenomenon of Mugabe -- Thoughts on leadership and the future -- Recent developments.
Includes bibliographical references (pages 181-182) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: Mugabe, Robert Gabriel, -- 1924-2019.; Mugabe, Robert Gabriel, -- 1924-2019; Mugabe, Robert Gabriel; Since 1980; Presidents -- Zimbabwe -- Biography; Biography & autobiography -- Historical; History -- Africa -- South -- General; History -- Africa -- South -- Republic of South Africa; Politics and government; Presidents; Zimbabwe -- Politics and government -- 1980-; Zimbabwe; Biographies